Implementation of problem-based learning to improve problem-solving skills in vocational high school - Reny Murni Hidayati; Wagiran Wagiran (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
The learning process in Vocational High Schools must encourage students to have problem-solving skills needed in the industry through the application of appropriate learning models. In reality, the students' problem-solving skills in computer subjects and basic networks are still lacking, and the Problem-Based Learning learning model has never been applied. This research aims to understand the implementation of Problem-Based Learning (PBL) to improve students' problem-solving skills. This research is a class action research model of Kemmis and Taggart, carried out in three cycles; each cycle consisted of two meetings. The data were analyzed descriptively. The results show how PBL on computer subjects and basic networks can improve problem-solving skills. Improvements occurred in all aspects of observation. In problem-solving skills, 56.25% of the students in the above medium category in cycle I increased in cycle II to be 71.875% and increased again in cycle III to be 100%. This means that there are no students below the medium category in cycle III. PBL can improve problem-solving skills with the steps: (1) orienting students to the problem classically; (2) organizing students to study in a group work of four people and the division of tasks for each member; (3) guiding individual and group investigations on the same topic, discussed maximum in two groups; (4) developing and presenting the work done in front of the class with more time allocation in the discussion session; (5) analyzing and evaluating the problem-solving process that focuses on re-checking the results.